Comparative genre analysis of move patterns and metadiscorsal features of management forwards in corporate annual reports from Kuwait and Malaysia - Mobasher, Atefeh (2015)
Management foreword is an unedited qualitative section of Corporate Annual Reports (CARs). It is also considered as the most widely read section of CARs which could reveal the financial condition of the company in case their content was studied meticulously. So far, most of the studies have focused on the content of management forewords; however few studies considered its genre structure. The present study explored the genre structure of management forewords from Kuwait and Malaysia by conducting a move analysis. To that aim, the researcher proposed a move analysis model. The present model was an improvement over previous studies as the proposed moves had faithful strategies for their constituents. It consisted of six moves and was used for a comparative investigation between the genre structure of 31 samples from Kuwait and 33 samples from Malaysia. The frequency counts were done through corpus analysis software. The results of analysis showed variations in terms of the frequency of the moves, move-strategy combinations. The analysis also comprised of an investigation and comparison of move types (obligatory and optional) of management forewords which was not considered in previous studies. Considering three cutoff points (100%, 90% & 50%), the two sets of sample did not have any variations with regard to move type at 100% and 50% cutoff points and there were minor differences between them at 90% cutoff point. Finally, the metadiscoursal features of each move from Kuwait and Malaysia was investigated and compared following the framework proposed by Hyland and Tse (2004) which was not considered in previous studies on management forewords, either. The analysis revealed that the two sets of the samples did not reveal considerable variations with regard to the use of metadiscoursal items, yet were different in terms of the frequency of used items. The results also revealed that the frequency of metadiscourse items were low in this genre.Some of the contributions of the present study are in the proposing of a move analysis model specifically for management forewords with faithful constituents and in the identifying of some new strategies. The results and findings of the present study could be useful for the ESP practitioners and material designers who provide the course material for business students to make them aware of the conventions of writing effective management forewords.